«Jag är inte riktigt mig själv. Och det är jag glad för»: Kristina Lugn's Humour as Literal Language in Hej då, ha det så bra! and «Inte alls dåligt» - Smedberg Bondesson, Anna (Nordlit, 2023)
In Kristina Lugn’s poetry collection Hej då, ha det så bra! (2003), as well as in the posthumous ”Inte alls dåligt” (2022), her own poetics is pushed to its extreme. The non-literality of the metaphor as well as the absurdity of the literality is laid bare. According to Lars Elleström, Lugn’s poems accentuates ”man’s concrete physical, and thus also mental, conditions” (Elleström 2006, 28). In my article, this reasoning applies not only to the bodily metaphoric, but to the entire literal language.Ann-Helén Andersson formulates in her PhD thesis ”Jag är baserad på verkliga personer”. Ironi och röstgivande i Kristina Lugns författarskap that ”In Lugn’s texts, the comic can be seen as an element within a dominant ironic tendency.” (Andersson 2010, 115). Using Luigi Pirandello’s essay L’umorismo (1908) and the concept sentimento del contrario, I will instead argue that Lugn’s literal language, the object of my analysis, opens for a humorous, rather than ironic, effect which can make reality appear a little more tangible and graspable – in all its horrific absurdity.
Keywords: Pirandello; umorismo; Kristina Lugn; humour; metapoetry